Preoperative hemostasis assessment in adenotonsillar surgery: is it really necessary? - Gama, Rita; Medeiros, Nuno; Castro, Fernanda; Condé, Artur (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Background: Adenoidectomy, tonsillectomy and adenotonsillectomy are among the most frequently performed procedures in otorhinolaryngology. Postoperative hemorrhage is, undoubtedly, the most feared complication of this kind of surgery. The authors aim to clarify the role of preoperative hemostatic assessment in adenotonsillar surgery, by reviewing the available literature on the subject. Methods: Articles adressing preoperative assessment on adenotonsillar surgery were searched in PubMed® database, since its publication till April 2020. Results: The role of hemostasis preoperative assessment in adenotonsillar surgery is still controversial, since some authors recommend its application in a selective range of patients, while others support its universal use. Most studies showed that a normal hemostatic study does not exclude the possibility of an hemostatic disease, and that most changed results are not correlated with the probability of postoperative hemorrhage. Hence, international recommendations discourage the screening of otherwise healthy patients, although most health care professionals continue to conduct preoperative tests in a systematic manner. Conclusions: The authors emphasize the need to discuss the subject and to protocol the preoperative approach for these patients, given the confusing and divergent existing data, in such frequently performed procedures in the otolaryngology field.